(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In fact, the Internet is a channel for the transfer of mental and behavioral patterns that affect the cultural context of our society, which has led to changes in the patterns of cultural values and structures and behaviors at the level of members of Syrian society in general and young Syrians in particular. If young people in certain parts of the world are considered to be the creators and manufacturers of this new technology, today’s young people are considered to be consumers, and even more so than their often passive recipients. This situation has been a concern and concern of many institutions and at different levels and educators are researchers because of fear of the negative effects of psychologically, socially and economically on our youth in terms of identity, values and behavior. These challenges were a concern for everyone and had to be sought to understand and see the dimensions and the development of strategies and plans that limit the extent possible impact of this network to them, especially in an era that we can not prevent them from communicating with it